Arm Cycle Ergometer Electro-Mechanical System Design For Post-Stroke Medical Rehabilitation - Kristanto, Yosua Hendra; Kawitana, Welina Ratnayanti; Prijo, Tri Anggono (Indonesian Applied Physics Letters, 2021)
This study was done to make the electro-mechanical arm ergometer cycle system used as post-stroke patient physiotherapy. The management system was expected to set the rotary frequency according to the therapeutic needs. To set the frequency of the rotation, the PID control with rotation sensor was used as feedback. The rotating sensor used consisted of the optocoupler and a rotary encoder. Based on the research that has been done, obtained constants of Kp = 0055, Ki and Kd = 2545 = 0.00005. Constants were selected because they were the most optimum constant trial and error method. The system is made to have a more significant percentage of error of 5%. In this study, the response time values obtained for each additional mass of the load at each frequency setting result are increased.